KUTA-TRANSPARAN: Model Sistem Informasi Terintegrasi untuk Pencegahan Pungutan Liar pada Desa Wisata Berbasis Fraud Risk Management dan Akuntansi Digital - Fauzan Nurahmadi; Muhammad Irfan Sarif; Pauzi Ibrahim Nainggolan; T. Henny Febriana Harumy (Universitas Methodist Indonesia, 2026)
Illegal levies (pungli) in tourism village public services threaten transparency and accountability of village governance. This study develops the KUTA-TRANSPARAN Framework as an integrated information system model for preventing pungli, with a case study in Kutagugung Village, Karo Regency, North Sumatra. The research adopts Participatory Action Research (PAR) integrated with Design Science Research (DSR), the GAO Fraud Risk Management Framework, and the Technology Acceptance Model (TAM), with hypothesis testing using Structural Equation Modeling–Partial Least Squares (SEM-PLS) on a sample of 120 respondents (purposive sampling). The framework encompasses three dimensions: (1) technology, based on mobile applications and blockchain; (2) business processes, covering prevention (Electronic Village Services/EVS, Electronic Tourism Retribution/ETR, Digital BUMDes Accounting/DBA), detection (real-time monitoring, whistleblowing), and response (auto-sanctions); and (3) institutional, covering policy and transparency culture. The ETR module achieved 81.3% transaction time efficiency (reduced from 15–30 minutes to 2.8 minutes), while the EVS module achieved 70% administrative processing efficiency (reduced from 3–7 days to 4.2 hours). Pilot results show a 23% increase in village retribution revenue (from IDR 12.3 million to IDR 15.1 million per month) attributable to the elimination of revenue leakage. All five hypotheses were supported, with the integration of management information systems and digital accounting demonstrating the strongest effect on financial accountability (β=0.79; p<0.001). The theoretical contribution lies in an interdisciplinary framework integrating informatics management and accounting computerization for fraud prevention in tourism villages. Practically, the blueprint supports SDGs Goal 16 and Goal 17.